Improving English Vocabulary Through Word Chain Game in an Inclusive School in Bandar Lampung - Musiman, Musiman; Vernanda, Ganesa; Fitriani, Dhafiya (ELT-Lectura, 2025)
The purpose of the study is to find out whether word chain games can improve vocabulary mastery and to find out which word chain games are effective in improving vocabulary mastery. The results of this study can be used as input in the teaching and learning process, especially in teaching vocabulary. The results of this study can also be used to improve the quality of vocabulary learning. This research uses a quasi-experiment approach. There is only an experimental class without a control class. There are 3 main stages of research, namely pre test, treatment and post test. Pre test is conducted before treatment, while post test is conducted after treatment. The pre test will be conducted several times until the research subjects experience consistent conditions. The research subjects were 19 inclusive school students at X school in Bandar Lampung city who were taken by cluster random sampling. The results revealed that there was a significant effect on the use of word chain games in mastering vocabulary in inclusive classes. This can be seen from the difference in pre-test and post-test scores which shows an increase in learning achievement in respondents. In the inclusion class, students learn side by side in diversity. Although there are some students who have special needs, they can learn side by side. Through this game they can actively together build an attractive and more fun learning atmosphere. Keywords: vocabulary, word chain game, inklusi